2002
DOI: 10.1038/nn837
|View full text |Cite
|
Sign up to set email alerts
|

A specialization for relative disparity in V2

Abstract: Stereoscopic depth perception relies on binocular disparities, or small geometric differences between the retinal images of each eye. The most reliable binocular depth judgments are those that are based on relative disparities between two simultaneously visible features in a scene. Many cortical areas contain neurons that are sensitive to disparity, but it is unclear whether any areas show a specific sensitivity to relative disparity. We recorded from neurons in the early cortical visual area V2 of the awake m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
183
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(197 citation statements)
references
References 21 publications
13
183
1
Order By: Relevance
“…We characterized relative disparity only in a small number of the V2 neurons (n ϭ 17). Only four of these showed significant tuning for relative disparity, comparable with the previously reported proportion (Thomas et al, 2002). This small number does not allow us to draw definitive conclusions about the relationship between tuning for relative disparity and CP in V2.…”
Section: Effect Of Other Tuning Properties On Choice Probabilities In V2supporting
confidence: 57%
See 1 more Smart Citation
“…We characterized relative disparity only in a small number of the V2 neurons (n ϭ 17). Only four of these showed significant tuning for relative disparity, comparable with the previously reported proportion (Thomas et al, 2002). This small number does not allow us to draw definitive conclusions about the relationship between tuning for relative disparity and CP in V2.…”
Section: Effect Of Other Tuning Properties On Choice Probabilities In V2supporting
confidence: 57%
“…A previous study showed that a proportion of V2 neurons were specialized for signaling relative disparity (Thomas et al, 2002). We characterized relative disparity only in a small number of the V2 neurons (n ϭ 17).…”
Section: Effect Of Other Tuning Properties On Choice Probabilities In V2mentioning
confidence: 99%
“…Similarly, Hegde and Van Essen (2000) invoked the idea of convergence from V1 onto V2 cells to account for selectivity for complex contours. Similar schemes may also explain responses to motion borders (Marcar et al, 2000), illusory contours (von der Heydt et al, 1984(von der Heydt et al, , 1992, and relative disparity (Thomas et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…This study investigated the organization of the binocular RFs of neurons in the early visual cortex, which are the lowest-level building blocks of depth-information processing in the brain (Maunsell and Van Essen, 1983;Ohzawa et al, 1990;Janssen et al, 1999;Taira et al, 2000;Connor, 2001, 2002;Prince et al, 2002a,b;Thomas et al, 2002;Nguyenkim and DeAngelis, 2003;Tanaka and Ohzawa, 2006). By analyzing the responses to dynamic 2D dichoptic random-dot stimuli whose patterns were uncorrelated between the two eyes, binocular interactions were examined for a pair of both X and Y positions in the RFs of single neurons.…”
Section: Discussionmentioning
confidence: 99%